Meet me in the margins : a novel - Ferguson, Melissa (Assistant professor) (Thomas Nelson, 2022)
Savannah Cade's dreams are coming true. The Claire Donovan, editor-in-chief of the most successful romance imprint in the country, has requested to see the manuscript Savannah's been secretly writing while working as editor herself--except at her publishing house, the philosophy is only highbrow works are worth printing and commercial fiction, particularly romance, should be reserved for the lowest level of Dante's inferno. But when Savannah drops her manuscript during a staff meeting and nearly exposes herself to the whole company--including William Pennington, new publisher and son of the romance-despising CEO herself--she races to hide her manuscript in the secret turret room of the old Victorian office. When she returns, she's dismayed to discover that someone has not only been in her hidden nook but has written notes in the margins--quite critical ones. But when Claire's own reaction turns out to be nearly identical to the scribbled remarks, and worse, Claire announces that Savannah has six weeks to resubmit before she retires, Savannah finds herself forced to seek the help of the shadowy editor after all... -- back cover.